Effect of the antitussive glaucine on bronchomotor tone in man. Issue 7 (July 1983) - Constant, O; Slavin, B; Lehane, J R; Jordan, C; Jones, J G
Abstract : In view of the observation that the antitussive agent glaucine prevents histamine-induced bronchoconstriction in guinea pigs we investigated this agent for a possible peripheral action in man, using a new method for measuring changes in bronchomotor tone. The forced airflow oscillation method was used to determine respiratory resistance (Rrs) over a range of lung volumes (VL) in seven healthy supine subjects. Computer analysis of the hyperbolic relationship between Rrs and VL was used to determine the asymptotic resistance and yield estimates of lower airways conductance (Glaw). Specific lower airways conductance (sGlaw) was expressed as the slope of the linear plot of Glaw against VL and is a sensitive index of bronchomotor tone. After baseline measurements of sGlaw subjects received placebo or 60 mg glaucine orally according to a double-blind crossover protocol. Histamine, 500 micrograms, was inhaled 45 minutes later. Measurements of sGlaw were repeated every 10 minutes for two hours. Although there was a trend towards bronchodilatation after glaucine administration (sGlaw = 130% of baseline) there was no significant difference from the effect of placebo (sGlaw = 89% of baseline). After inhalation of histamine sGlaw fell to 26% of baseline after both glaucine and placebo (p less than 0.01). In a further study three subjects received glaucine and placebo according to an identical protocol except that the histamine was omitted. Again the increase in sGlaw failed to achieve significance. Glaucine does not affect the bronchoconstrictor response to histamine in man and there is no convincing evidence of an effect on resting bronchomotor tone.